The influence of tahfidz Al-Qur’an program management on students’ religious character - Muhamad Fathi; Wahyu Hidayat; Heny Mulyani (Curricula: Journal of Curriculum Development, 2025)
The decline in religious character among adolescents underscores the need to strengthen religious education as a strategy for fostering spirituality. Religious education plays a direct role in instilling the values of faith, piety, and noble morals. This study aims to examine the implementation of tahfidz program management, the level of religious character, and the influence between the two. This research used a quantitative approach with an ex post facto method. Data were collected through questionnaires and documentation from 80 students. Data analysis techniques included validity and reliability testing, indicator-level analysis, normality and linearity tests, simple linear regression, t-test, and the coefficient of determination using SPSS 27. The results showed that tahfidz program management was categorized as high, while the religious character was categorized as very high. The t-test showed a significance value indicating a significant influence. Tahfidz program management contributed to the variance in religious character. These findings affirm that structured tahfidz management, through planning, organizing, acting, and controlling, can effectively strengthen religious character and serve as a relevant strategy in character education within Islamic boarding schools.    Abstrak Menurunnya karakter religius di kalangan remaja menyoroti urgensi penguatan pendidikan agama sebagai strategi pengembangan spiritualitas. Pendidikan agama berperan langsung dalam menanamkan nilai keimanan, ketakwaan, dan akhlak mulia. Penelitian ini bertujuan untuk mengkaji implementasi manajemen program tahfidz, tingkat karakter religius, dan pengaruh antara keduanya. Penelitian ini menggunakan pendekatan kuantitatif dengan metode ex post facto. Data dikumpulkan melalui kuesioner dan dokumentasi dari 80 santri. Teknik analisis data meliputi uji validitas dan reliabilitas, analisis taraf indikator, uji normalitas dan linearitas, regresi linier sederhana, uji-t, dan koefisien determinasi dengan menggunakan SPSS 27. Hasil penelitian menunjukkan bahwa manajemen program tahfidz dikategorikan tinggi, sedangkan karakter religius dikategorikan sangat tinggi. Uji-t menunjukkan nilai signifikansi yang menunjukkan pengaruh yang signifikan. Manajemen program tahfidz berkontribusi terhadap varians karakter religius. Temuan ini menegaskan bahwa manajemen tahfidz yang terstruktur melalui perencanaan, pengorganisasian, penggerakan, dan pengendalian dapat secara efektif memperkuat karakter religius dan berfungsi sebagai strategi yang relevan dalam pendidikan karakter di lingkungan pesantren. Kata Kunci: karakter religius; manajemen program; tahfidz Al-Qur’an